Learning Stypes of Male and Female Students of Nepal - Rai, Amrit Kumar; Dhakal, Megha Raj (Journal of Advanced Academic Research, 2018)
Learning is natural phenomena starts with the birth; it is a gradual process of investigation of new knowledge. Every creature has their own learning styles as their biological and social nature. People have superior power to learn many things as they become interested. School is one platform to learn many things for the students. School creates the learning environment but learning style may be varied in student to student. The study aims to identify the learning styles of male and female students of public and private school of Nepal. Primary data were collected from Makwanpur, Chitwan, Gorkha and Dhading Districts among Chepang Community. The study is done among the 368 students of four districts. The three types of learning styles: Visual, Auditory, and Kinesthetic (VAK) model developed by Neil Fleming was used in field for data collection. The result shows that there is no significant different between male and female students regarding their learning styles. It indicates that achievement and performance of male and female is similar. In Nepalese society, there are some gender differences in social relationship. Still, in most of the society, daughters are given less priority for their growth and development because of the patriarchal concept of society but the study has given the different result than the general concept. It is shown that a daughter can give better result if she will get better learning environment. The result has challenged the discriminatory gender relation in society.